2020
DOI: 10.1101/2020.06.23.20137455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitivity of different RT-qPCR solutions for SARS-CoV-2 detection

Abstract: Objectives: The ongoing COVID-19 pandemic continues imposing a demand for diagnostic screening. In anticipation that the recurrence of outbreaks and the measures for lifting the lockdown worldwide may cause supply chain issues over the coming months, we assessed the sensitivity of a number of one-step retrotranscription and quantitative PCR (RT-qPCR) solutions to detect SARS-CoV-2. Methods: We evaluated six different RT-qPCR alternatives for SARS-CoV-2/COVID-19 diagnosis based on standard RNA extractions. That… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 10 publications
0
27
0
1
Order By: Relevance
“…The global spread of a new type of coronavirus, SARS-CoV-2, causing the respiratory disease COVID-19 [ 1 , 2 , 3 , 4 ] mobilized both the public and private sector and resulted in a rapid development of solutions focused on SARS-CoV-2 detection and analysis. Next to a number of solutions utilizing the advantages of RT-qPCR techniques for SARS-CoV-2 detection [ 5 , 6 ], the next-generation sequencing (NGS)-based protocols allows the analysis of SARS-CoV-2 genome evolution and variability and the monitoring of its spread within the global population (Nextstrain; ) [ 7 , 8 ]. These knowledges address the need to elucidate its genomic characteristics (GISAID; ) in order to ensure the efficiency of RT-qPCR testing, assess its transmission through clonal events, and develop a reliable vaccination protocols future therapies, especially considering the fact that RNA viruses are prone to accumulate variants in its genome in a relatively short timeline, which in the case of SARS-CoV-2 is also related to its capacity to proofread and remove mismatched nucleotides during genome replication and transcription [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The global spread of a new type of coronavirus, SARS-CoV-2, causing the respiratory disease COVID-19 [ 1 , 2 , 3 , 4 ] mobilized both the public and private sector and resulted in a rapid development of solutions focused on SARS-CoV-2 detection and analysis. Next to a number of solutions utilizing the advantages of RT-qPCR techniques for SARS-CoV-2 detection [ 5 , 6 ], the next-generation sequencing (NGS)-based protocols allows the analysis of SARS-CoV-2 genome evolution and variability and the monitoring of its spread within the global population (Nextstrain; ) [ 7 , 8 ]. These knowledges address the need to elucidate its genomic characteristics (GISAID; ) in order to ensure the efficiency of RT-qPCR testing, assess its transmission through clonal events, and develop a reliable vaccination protocols future therapies, especially considering the fact that RNA viruses are prone to accumulate variants in its genome in a relatively short timeline, which in the case of SARS-CoV-2 is also related to its capacity to proofread and remove mismatched nucleotides during genome replication and transcription [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The duplex set-up reduced reagents usage as well as processing time, while maintaining a high detection rate, modest analytical sensitivity and a much lower cost. Even though the test still has room for improvement, it showed a high sensitivity which is well within the parameters for diagnostics and comparable to other commercial kits [16][17]. Many in-house tests can be found in literature, however, to our knowledge their viability has not been explored in Ecuador.…”
Section: Discussionmentioning
confidence: 71%
“…3). An excellent starting point would be an exploratory study on selection of RT-qPCR mixes which has been shown to signi cantly alter the sensitivity of a COVID diagnostic [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples’ RNA were purified with Quick-RNA Viral Kit (Zymo Research, Irvine, CA, USA), and viral detection was performed with AgPath-ID One-Step RT-PCR reagents (ThermoFisher Scientific, Austin, TX, USA), according to manufacturers’ instructions. A 20 µL total reaction volume containing 5.0 µL purified RNA, 400 nM primers, and 200 nM probes following the CDC USA protocol targeting the N1 and N2 sequences of the SARS-CoV-2 nucleoprotein gene [8] , with a sensitivity of 75-80% [9] . Cycle thresholds < 40 were considered positive.…”
Section: Methodsmentioning
confidence: 99%